Changes in physicochemical properties and protein structure of surimi enhanced with camellia tea oil. (October 2017) - Zhou, Xuxia; Jiang, Shan; Zhao, Dandan; Zhang, Jianyou; Gu, Saiqi; Pan, Zhiyan; Ding, Yuting
Abstract: The objective of this study was to determine the effects of different concentrations of camellia tea oil on surimi gel physicochemical properties and protein secondary structure. With the increase of camellia tea oil concentration (0–8 g/100 g of surimi), surimi gel hardness, whiteness, WHC, overall acceptability, storage modulus (G′) and the indexes of ionic bonds and hydrophobic interactions were increased significantly (P < 0.05). Cryo-scanning electron microscopy (Cryo-SEM) showed that the oil occupied the void spaces of the protein matrix and formed a firmer structure. The Raman spectroscopy study showed that there was a decreased trend in α-helix content and increased trend in β-sheet content in surimi protein as the oil content increased. Correlation analysis showed that the hardness was negatively correlated to the α-helix content (r = −0.958, P < 0.01) and positively correlated to the β-sheet content (r = 0.958, P < 0.01) and hydrophobic interactions (r = 0.944, P < 0.01) of surimi gels. These results suggest that the presence of the oil could change the micro-environment and molecular structure of surimi proteins and further affect the physicochemical properties of surimi gels. In general, when the concentration of camellia tea oil was 8 g/100 g of surimi, the surimi gel showed the most favorable properties. Highlights: Camellia tea oil could improve the physicochemical properties of surimi gel. Oil could change the ionic, hydrogen bond, and hydrophobic interactions of surimi gel. Oil decreased the α-helix content and increased the β-sheet content in surimi protein. The hardness of surimi gel was positively correlated to its β-sheet content. An 8% content of camellia tea oil gives surimi gel the best properties.